Анализ подходов к управлению рисками проектов разработки сложной техники - Ченарани, Али; Дружинин, Евгений Анатольевич; Погудина, Ольга Константиновна (НТУ "ХПИ", 2016)
Рассмотрены некоторые особенности проектов создания сложных технических систем (на примере эскизного проектирования авиационных двигателей) которые указывают высокую степень неопределенности и риска в данной стадии жизненного цикла изделия. Проведен обзор литературы на предмет анализа подходов и стандартов управления рисками проекта с целью проверки возможности их использования в дальнейших исследованиях. Представлены некоторые нетрадиционные подходы к управлению рисками и неопределенностями проектов.

The importance of complex technical products and the role of design phase in developing these products are stated. Some specific features which indicate the high degree of uncertainty and risk in this phase (preliminary design of aviation engines as a more specific case) are mentioned. Considering the importance of risk management in these situations, literature review and analysis in the field of risk management approaches and standards are performed in order to evaluate the possibility of using or developing them in further research. Differences and similarities between these approaches and standards as well as different tools and solutions are investigated. Some new approaches and trends for managing risk and uncertainty in projects are presented.
Analysis of approaches to risk management in projects of developing complex technical products
Keywords: неопределенность; двигатель авиационный; стандарт; проектирование эскизное; project management; uncertainty; complex machinery; aircraft engine; preliminary design